Dietary supplementation of mulberry leaf oligosaccharides improves the growth, glucose and lipid metabolism, immunity, and virus resistance in largemouth bass (Micropterus salmoides) - Zhou, Donglai; Zhong, Wenhao; Fu, Bing; Li, Erna; Hao, Le; Li, Qingrong; Yang, Qiong; Zou, Yuxiao; Liu, Zhenxing; Wang, Fubao; Liao, Sentai; Xing, Dongxu (Frontiers in Immunology, 2025)
This study investigated the effects of dietary supplementation of mulberry leaf oligosaccharides (MLO) on the growth performance, serum biochemistry, glucose and lipid metabolism, antioxidant activity, liver health, and virus resistance in largemouth bass (Micropterus salmoides). The fish were fed with CK (basal diet), MLOL (basal diet supplemented with 0.5%MLO), and MLOH (basal diet supplemented with 1.0% MLO) for 80 days, and then subjected to a 21-day viral challenge experiment. The results showed that MLO supplementation had no adverse effect on the weight gain rate, specific growth rate, feed intake, and condition factor (P > 0.05), but significantly decreased the feed conversion rate and viscerosomatic index (P< 0.05). Moreover, the MLOL and MLOH group had significantly lower contents of triglyceride, blood glucose, and malondialdehyde and activities of serum alanine aminotransferase and aspartate aminotransferase, while significantly higher levels of serum and liver total superoxide dismutase and lower levels of glutathione than the CK group (P< 0.05). MLO supplementation significantly up-regulated the relative expression of glycolytic genes gk and pfk and lipid catabolism genes ppar-α and cpt-1, while obviously down-regulated that of acc, fas, and dgat related to fatty acid synthesis in the liver tissue (P< 0.05). In terms of liver health, MLO supplementation significantly up-regulated the relative expression of anti-inflammatory cytokines il-10 and tgf-β, while decreased that of pro-inflammatory cytokines nf-κb, il-8, and tnf-α in the liver tissue (P< 0.05). The viral challenge test showed that MLO supplementation significantly improved the survival rate of M. salmoides after largemouth bass ranavirus (LMBV) infection. Dietary MLO supplementation promoted liver glucose and lipid metabolism, and improved the immunity and resistance of M. salmoides to LMBV by regulating the PPAR signaling way and inhibiting the NF-kB signaling pathway. The appropriate addition amount of MLO to the diet was determined to be 1.0%.